Trend of Cesarean Section Rates and Correlations with Adverse Maternal and Neonatal Outcomes: A Secondary Analysis of Thai Universal Coverage Scheme Data - Liabsuetrakul, Tippawan; Sukmanee, Jarawee; Thungthong, Jutatip; Lumbiganon, Pisake (American Journal of Perinatology Reports, 2019)
Objectives The main purpose of this article is to estimate the trend and projection of cesarean section rates (CSRs) and explore correlations between CSRs with adverse maternal and perinatal outcomes, namely maternal mortality ratios (MMRs), rates of postpartum hemorrhage (PPH), neonatal mortality rates (NMRs), and birth asphyxia per 1,000 live births across all regions of Thailand.Study design A secondary analysis of the hospital-based database of pregnant women and newborns under the Thai Universal Coverage Scheme between January 2009 and December 2017 was conducted.Results Overall annual CSR significantly increased from 23.2% in 2009 to 32.5% in 2017. With the same rate of increase, the CSR of 59.1% was projected by the year 2030 that could be reduced to 30.0% if an annual rate of CS reduction of 1% was assumed using Joinpoint regression. The increasing CSRs were significantly correlated with higher MMRs (r= 0.20, p = 0.03) and birth asphyxia (r= 0.39, p < 0.001). The correlation trends were similar when the analyses were stratified by year in the majority of years. Overall correlations between CSRs and rates of PPH or NMRs were not statistically significant.Conclusion CSRs in Thailand continuously increased and were correlated with adverse maternal and perinatal outcomes. More effort at the national level to reduce unnecessary CS is urgently required.
Keywords: cesarean section rates; maternal and perinatal outcomes; trend; Universal Coverage Scheme